2017
DOI: 10.1007/s00424-017-1989-8
|View full text |Cite
|
Sign up to set email alerts
|

Na +/Ca2+ exchangers and Orai channels jointly refill endoplasmic reticulum (ER) Ca2+ via ER nanojunctions in vascular endothelial cells

Abstract: We investigated the role of Na+/ Ca2+ exchange (NCX) in the refilling of endoplasmic reticulum (ER) Ca2+ in vascular endothelial cells under various conditions of cell stimulation and plasma membrane (PM) polarization. Better understanding of the mechanisms behind basic ER Ca2+ content regulation is important, since current hypotheses on the possible ultimate causes of ER stress point to deterioration of the Ca2+ transport mechanism to/from ER itself. We measured [Ca2+]i temporal changes by Fura-2 fluorescence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…The amplitude of the Ca 2+ elevation was, however, significantly lower whereas its duration was dramatically curtailed. Third, the selective blockade of the reverse mode NCX with KB-R mimicked the effect of Na + withdrawal on NaHS- and capsaicin-induced intracellular Ca 2+ signals [ 62 , 64 ], thereby confirming that the reverse mode NCX is recruited by TRPV1-mediated extracellular Na + entry to sustain the ensuing increase in [Ca 2+ ] i . These data are consistent with those reported in native endothelium of rat aorta [ 62 ] and confirm a recent report on in the CRC cell line, DLD1 [ 20 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The amplitude of the Ca 2+ elevation was, however, significantly lower whereas its duration was dramatically curtailed. Third, the selective blockade of the reverse mode NCX with KB-R mimicked the effect of Na + withdrawal on NaHS- and capsaicin-induced intracellular Ca 2+ signals [ 62 , 64 ], thereby confirming that the reverse mode NCX is recruited by TRPV1-mediated extracellular Na + entry to sustain the ensuing increase in [Ca 2+ ] i . These data are consistent with those reported in native endothelium of rat aorta [ 62 ] and confirm a recent report on in the CRC cell line, DLD1 [ 20 ].…”
Section: Discussionmentioning
confidence: 88%
“…The amplitude of the Ca 2+ signal in the responding cells (66 out of 245; 27%) was significantly ( p < 0.05) smaller as compared to the control ( Figure 11 C). In order to confirm NCX role in NaHS-dependent Ca 2+ signaling, we probed the effect of KB-R 7943 (20 μM, 20 min), a selective inhibitor of the reverse-mode NCX at this concentration [ 62 , 64 ]. In agreement with the results presented above, NaHS failed to elicit an [Ca 2+ ] i elevation in 146 out of 182 (80.2%) cells pre-treated with the blocker ( Figure 11 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the dramatic increase in plateau amplitude observed in the presence of CPA is not due to further SOCE activation, but to the impairment of Ca 2+ sequestration into ER lumen, which results in Ca 2+ accumulation within the cytosol. It has been shown that ER Ca 2+ refilling occurs at plasma membrane/ER nanojunctions [55,56], which recruit SERCA upon massive ER Ca 2+ depletion [57,58], in vascular endothelial cells. Accordingly, InsP 3 -induced drop in ER Ca 2+ concentration causes SERCA migration and co-localization with Stim1 and Orai1, thereby resulting in more efficient Ca 2+ pumping into the ER [57,58].…”
Section: Ca 2+ Clearing In Lzdf Rats: the Control Conditionmentioning
confidence: 99%
“…Herein, STIM1 physically interacts with and gates Orai1, which provides the pore forming subunit of a store-operated channel termed the Ca 2+ release-activated Ca 2+ (CRAC) channel. STIM1 and Orai1 were also shown to mediate SOCE in HAECs [ 105 , 173 ], in human pulmonary artery endothelial cells (HPAECs) [ 170 ], and in the HUVEC-derived endothelial cell line, EA.hy926 [ 174 , 175 ]. Vascular endothelial cells also express the STIM1 and Orai1 paralogues, i.e., STIM2, Orai2, and Orai3 [ 109 , 110 , 173 ].…”
Section: Ros Modulate Store-operated Ca 2+ Entry In Vascular Endothelial Cellsmentioning
confidence: 99%